Influence of Finite Size Effects on the Fulde-Ferrell-Larkin-Ovchinnikov State (Communications in Computational Physics, 2018)
The Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state is the superconductingphase for which the Cooper pairs have a non-zero total momentum, depending on thesplitting of the Fermi surface sheets for electrons with opposite spin. In infinite systemsthe momentum is a continuous function of the temperature. In this paper, we haveshown how the finite size of the system, through the discretized geometry of the Fermisurface, affects the physical properties of the FFLO state by introducing discontinuitiesin the Cooper pair momentum. Our calculations in an isotropic system show that thesuperconducting state with two opposite Cooper pair momenta is more stable thanstate with one momentum also in nano-size systems, where finite size effects play acrucial role.